2021
DOI: 10.3390/ijms22094569
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Leptin in Fetal Growth during Pre-Eclampsia

Abstract: Leptin is secreted by the placenta and has a multi-facetted role in the regulation of functions related to pregnancy. Metabolic disorders and insufficient homeostatic compensatory mechanisms involving leptin during pregnancy play a decisive role in the development of pre-eclampsia (PE) and give rise to compromised intrauterine growth conditions and aberrant birth weight of offspring. This review was compiled to elucidate the metabolic background of PE and its relationship with adverse intrauterine growth condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 118 publications
0
31
0
Order By: Relevance
“…IUGR, due to uteroplacental insufficiency, results in a nephron deficiency and glomerular hypertrophy in both male and female rats [ 72 ]. Human studies appear to support these data because infants with SGA, which is often associated with placental insufficiency, have an increased risk of end-stage kidney disease compared to controls [ 73 ].…”
Section: Consequences For Offspringmentioning
confidence: 99%
“…IUGR, due to uteroplacental insufficiency, results in a nephron deficiency and glomerular hypertrophy in both male and female rats [ 72 ]. Human studies appear to support these data because infants with SGA, which is often associated with placental insufficiency, have an increased risk of end-stage kidney disease compared to controls [ 73 ].…”
Section: Consequences For Offspringmentioning
confidence: 99%
“… 45 , 46 LEP encodes leptin, which is a hormone released by the placenta and is important in fetal growth throughout the entirety of pregnancy. 47 LEP up-regulation in IUGR placentas was reported in another 3 studies. 48 - 50 Leptin is crucial in placental development and function.…”
Section: Discussionmentioning
confidence: 71%
“…Maternal plasma leptin concentration was associated with infants change in weight ( p = 0.017) and confirmed in the partial correlation when adjusting for time and neonate type (−0.27). Previous studies reported no association between maternal leptin concentration and birthweight/weight change [ 6 , 20 ]; or higher incidence of IUGR neonate in pre-eclamptic pregnancy, if maternal serum leptin levels were elevated [ 21 ]. Moreover, a significant rate of low-birth-weight infants in non-diabetic mothers with high leptin plasma concentration was reported [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%